The Relationship Of The Role Of Parents On The Reproductive Health Of Adolescents In Batumbulan Ii Village, Babussalam District, Southeast Aceh District - Yessy Syahradesi Br Tambunan; Yusnika Damayanti (Jurnal EduHealth, 2023)
Unhealthy reproductive health behavior among teenagers, especially unmarried teenagers, is increasing. The impact of unhealthy reproductive health behavior causes teenagers to engage in premarital sex and promiscuity among teenagers. One of the factors that influences reproductive health behavior in adolescents is the role of parents. The aim of this research is to determine the relationship between the role of parents and adolescent reproductive health in Batumbulan II Village, Babussalam District, Southeast Aceh Regency. The population in this study was 557 parents who had teenage children aged 16-19 years in Batumbulan II Village, Babussalam District. The sample in this study was parents who have teenage children, totaling 85 respondents. The sampling method is using random sampling. The research was carried out in Batumbulan II Village, Babussalam District, Southeast Aceh Regency. The research results showed that the role of parents on adolescent reproductive health showed that (80%) had a positive role and (20%) had a negative role on adolescent reproductive health. The results of research on adolescent reproductive health behavior showed that (82.35%) showed good reproductive health behavior and (17.65%) had poor reproductive health behavior. The conclusion from the research is that there is a very significant relationship between the role of parents and adolescent reproductive health. So it is hoped that teenagers and parents will better understand the knowledge, attitudes and actions of teenagers in order to reduce the occurrence of unhealthy adolescent reproductive health behavior.